Utilization patterns of Chiranjeevi Swasthya Bima Yojana in Rajasthan during financial year 2023 to 2024: a cross-sectional study at a tertiary care hospital - Singh, Shalini; Rathore, Monika; Raj, Ankit (International Journal Of Community Medicine And Public Health, 2024)
Background: Publicly funded health insurance (PFHI) is considered a key policy tool to provide financial protection to households seeking healthcare. The state government of Rajasthan has launched Mukhya Mantri Chiranjeevi Swasthya Bima Yojana (CSBY), with a cover of 25,00,000 INR per family per year, that makes it one of the largest PFHI in world by cost-coverage. However, there is an evidence-gap on utilization patterns and consequent need of higher-rate packages in state-PFHIs. A study was designed with the objective to describe the utilization pattern of CSBY in Rajasthan. Methods: The cross-sectional study was conducted at Sawai Man Singh Hospital in Jaipur, the highest public tertiary care institute of Rajasthan. The data on CSBY hospitalisations was collected from Chiranjeevi portal for financial year 2023-2024. Summary statistics were used to describe the variables such as age and gender of beneficiaries and medical specialities and cost details of packages utilised. Results: The mean age of patients was 45.9 (±20.0) years and 62.1% were males. The top specialty by volume of admission was general medicine (14.2%) and by cumulative cost of packages utilized was cardiology (22.0%). The median cost of packages utilized per hospitalization was 12,200 INR. 96.8% of beneficiaries utilized the services at a cumulative cost of up to 1 lakh INR and only 0.01% patients utilized more than 5 lakh INR. Conclusions: The study found higher utilisation of highly-specialised services over broad-specialties and an underutilisation of higher-rate packages, demonstrating a gap in perceived need of higher-rate packages in the state.